Results of construction of correlation fields with trend lines and determination of direction of relationships between studied indicators - Sirman, Y.; Preys , N.; Savytskyi, I. (Journal of Education, Health and Sport, 2021)
The aim of work is construction of correlation fields with trend lines and determination of the directionality of relationships between the investigated indicators of endothelial dysfunction, hypoxia and oxidative stress. Our results indicate that Willebrand factor, endothelin-1, 2,3-diphosphoglycerate, MDA, diene conjugates and eNOS are informative markers in the pathogenesis of experimental diabetic retinopathy. As a result of the research, it was established that there is a direct linear relationship between the Willebrand factor indicator and malondialdehyde, since the points of the correlation field are practically located on a straight line. We trace a similar type of direct linear relationship between Willebrand factor and diene conjugates. The specified results confirm the mutually aggravating relationship between the development of endothelial dysfunction and oxidative stress. We trace an inverse linear relationship between Willebrand factor and peroxidase. With an increase in Willebrand factor indicators by stages, we trace a decrease in peroxidase indicators, which indicates a relationship between endothelial dysfunction and a weakening of antioxidant protection. As a result of the study, it was established that the first two indicators: malondialdehyde and diene conjugates have an almost direct linear relationship with endothelin-1 indicators. These results confirm the relationship between the functional and structural state of the endothelium and the development of oxidative stress. It was established that the peroxidase indicator has an inverse linear relationship with the endothelin-1 indicators, which, as in the case of the Willebrand factor, indicates a violation of antioxidant protection in the event of endothelial dysfunction. As a result of the analysis of the dependence of the indicators of 2,3 diphosphoglycerate, Willebrand factor and eNOS, it was found that in the first two pairs of indicators, there is an inverse linear relationship between the indicators. As eNOS levels increase by stage, levels of 2,3 diphosphoglycerate and Willebrand factor decrease. In the case of an inverse relationship between the parameters of the Willebrand factor and eNOS, a practically functional connection is observed, since the coefficient of determination is almost 1. The obtained results indicate that the violation of the structural and functional state of the endothelium and the development of hypoxia are interconnected with the violation of the physiological pathway of oxide synthesis nitrogen. The relationship between the indicators of 2,3 diphosphoglycerate and the Willebrand factor was revealed, which has a direct relationship between the variables, which once again confirms the aggravating interaction between hypoxia and endothelial dysfunction.